Chemical fingerprints and implicated cancer risks of Polycyclic aromatic hydrocarbons (PAHs) from fine particulate matter deposited in human lungs. (March 2023) - Zhang, Xiangyuan; Leng, Siwen; Qiu, Mantang; Ding, Yifan; Zhao, Lin; Ma, Na; Sun, Yue; Zheng, Zijie; Wang, Shaodong; Li, Yun; Guo, Xuejun
Abstract: Exposure to fine particles (PM2.5 ) and associated PAHs are frequently linked with lung cancer, which makes the understanding of their occurrence and health risk in human lungs urgently important. Using the ultrasonic treatment and sequencing centrifugation (USC) extraction method coupled with gas chromatography-tandem mass spectrometry (GC - MS/MS) analysis, we revealed the molecular fingerprints of PM-accumulated PAHs in human lungs from a cohort of 68 patients with lung cancer in a typical air-polluted region, China. Sixteen priority PAHs can be grouped by concentrations as ∼ 1 × 10 4 ng/g (ANT/BkF/ACE/DBA/BgP/PHN/PYR), 2–5 × 10 3 ng/g (BaP/FLE/NaP/BbF), and ∼ 1 × 10 3 ng/g (IND/Acy/CHR/FLT/BaA). The sum concentration of 16 PAHs was approximately equaled to 13% of those in atmospheric PM2.5, suggesting significant pulmonary leaching of PAHs deposited in lungs. Low- and high-molecular weight PAHs accounted for ∼ 41.8% and ∼ 45.1% of the total PAHs, respectively, which indicated that atmospheric PM2.5, tobacco and cooking smoke were likely to be important sources of pulmonary PAHs. The evident increasing concentrations of NaP and FLE in pulmonary PM were significantly correlated with smoking history among smokers. The implicated carcinogenic potency of PM-accumulated PAHs among the participants aged 70–80 was 17 times that among participants aged 40–50 on the basis of BaP equivalent concentration (BaPeq) evaluation. The particulate enrichment factor ( EFP ), the PAH content in pulmonary PM relative to the bulk lung tissue, was equaled to 54 ∼ 835 and averaged at 436. The high value of EFP suggested that PAHs were essentially accumulated in pulmonary PM and exhibited a pattern of "hotspot" distribution in the lungs, which would likely increase the risk of monoclonal tumorigenesis. The chemical characteristics of PM-accumulated PAHs in human lungs together with their implicated lung cancer risks could provide significant information for understanding health effects of particulate pollution in the human body.